THE STUDY OF MARKET TIMING IMPLEMENTATION IN INDONESIAN STOCK MARKET - Salman Fajri; Tony Irawan; Trias Andati (Jurnal Manajemen Indonesia, 2019)
This study is intended to discuss about implementation of market timing as an investment alternative strategic in Indonesian Stock Market. Market timing is procedure for changing portfolio asset allocation to deal with changes in business cycle. The market timing indicator used in this study is interest rate of Bank Indonesia. The active portfolio consist of IHSG and bond for simple rotation strategy. Sector rotation strategy consist of cyclical and non cyclical sector index. The dissecting cycle analyse by two methods, Hamilton Filter and indicator change assumptions. The secondary data used in this study have a span of time from January 2005 - December 2017. The result showed that active strategies produced better performance than passive strategy, and sector rotation were the best performance among other alternative strategies. Optimal performance of simple rotation occurs when change of variable BI rate by ±2% and optimal performance of sector rotation occurs when change of variable BI rate by ±4%. Keywords—Hamilton Filter; Market Timing; Sector Rotation; Simple Rotation AbstrakPenelitian ini bertujuan untuk membahas tentang penerapan market timing sebagai tindakan strategi investasi aktif di pasar modal Indonesia. Market timing merupakan prosedur perubahan alokasi aset portfolio untuk menghadapi perubahan siklus bisnis di suatu negara. Indikator market timing yang digunakan dalam penelitian ini adalah suku bunga acuan Bank Indonesia. Portfolio aktif terdiri dari IHSG dan obligasi untuk strategi aktif rotasi sederhana dan indeks sektor siklikal dan non siklikal untuk rotasi sektoral. Pemilahan siklus dilakukan dengan dua metode yaitu Hamilton Filter dan asumsi perubahan variabel indikator. Seluruh data sekunder yang digunakan dalam penelitian ini memiliki rentang waktu dari Januari 2005 - Desember 2017. Hasil penelitian menunjukkan bahwa strategi aktif menghasilkan kinerja lebih baik relatif terhadap strategi pasif, dan strategi rotasi sektoral secara keseluruhan lebih baik dibandingkan dengan alternatif strategi lain. Strategi rotasi sederhana optimal pada penggunaan asumsi perubahan variabel ±25 bps (basis point) dan strategi rotasi sektoral optimal pada penggunaan asumsi perubahan variabel ±100 bps (basis point). Kata kunci— Hamilton Filter, Market Timing, Rotasi Sederhana, Rotasi Sektoral